Two new species of Papeocoris (Hemiptera: Heteroptera: Coreidae: Coreinae: Nematopodini) from Peru - Brailovsky, Harry (Zootaxa, 2013)
Two new species of Papeocoris are described from Peru, P. nitens sp. nov. and P. vittatus sp. nov. A key to species is provided together with dorsal view photographs.